Quality and storability of onion (Allium cepa L.) as influenced by varieties and household organic mulches - Md Harun Ar Rashid; Tangida Akter; Rabbani, Md Golam; Mst Tamanna Tasmim; Nahar, Ashrafun (Research in Agriculture Livestock and Fisheries, 2023)
An experiment was conducted to study the effects of varieties and household organic mulches on growth and yield of onion at the Horticulture Farm of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from October 2020 to March 2021. The experiment consisted of three onion cultivars of Bangladesh viz. Taherpuri, BARI Piaz 1 and BARI Piaz 4, and five household organic mulches, viz. T0 = Control (no mulching), T1 = vegetables wastes, T2 = rice straw, T3 = banana leaf and T4 = water hyacinth. The two-factor experiment was carried out in Randomized Complete Block Design with 3 replications. Results revealed that the parameters under study showed significant variation between onion varieties and mulching. Results showed that the highest percent of weight loss of bulbs (31.19%) was observed in V3T4 followed by V3T1 (29.89%) and the lowest percentage of weight loss of bulbs (24.66%) was observed in V1T1. The highest percentage of dry matter content of bulb (13.13%) was recorded in V3T4 followed by V3T1 (12.54%) and the lowest percent dry matter content of bulb (8.08%) was observed in V1T0. The highest percentage of splitted bulb (10.33%) was observed in V3T4 followed by V3T1 (9.33%) and the lowest percentage of splitted bulb (1.33%) was observed in V1T0 (Table 4). On the other hand, the highest percentage of rotten bulb (9.00%) was observed in V3T0 followed by V2T0 (8.33%) and the lowest percentage of rotten bulb (2.00%) in V1T2. Therefore, the combined use of water hyacinth along with Taherpuri was found to be better with respect to the quality and storability of onion. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 123-131